An Australian study of delusional disorder in late life. (29th April 2020) - Nagendra, Janani; Snowdon, John
ABSTRACT: Objectives: There is a paucity of available research to guide clinical practice in delusional disorder (DD), particularly in late life. This study aimed to evaluate antipsychotic use and treatment outcomes in patients with DD aged 65 years and older. Secondarily, we sought to examine associated clinical features and socio-demographic variables. Design and setting: This descriptive study reviewed all consecutive cases of DD referred to an Australian old age psychiatry service over a 12-year period. Fifty-five patients were assessed in the inpatient and/or community setting, with data verified from a review of all individual medical records. Measurements: Data were collected with respect to antipsychotic use, outcomes, and clinical features. Socio-demographic variables of DD cases were compared to a non-matched comparison group (n=278) and an age and gender matched comparison group with a 1:1 ratio (n=55). Results: The predominant type of DD was persecutory (87%). Non-prominent hallucinations were experienced by 18%, and depressive symptoms occurred in 22%. There was a statistically significant association between having DD and social isolation (χ 2 = 11.04 (DF=1) p<0.001; McNemar's test p <0.001). Atypical antipsychotic medication was prescribed in 32 cases, with follow-up permitted in 51 of the 55 cases (mean duration 36.6 months). Sustained recovery occurred in 20%, and improvement in an additional 35% of the study sample. Four patients subsequently developed dementia, and two developed mild cognitive impairment. Conclusions: Clinical improvement, including sustained recovery, occurred in more than half of those with late life DD. The majority of those who improved (96%) received atypical antipsychotics.